Foreign nationals as offenders and victims in Malaysian crime news - Misman, Norealyna; Mohd Adnan, Hamedi; Firdaus, Amira Sariyati; Ahmad, Che Mahzan (EDP Sciences, 2017)
Foreign nationals in Malaysia come from all corners of the world.They are here as migrant labour, highly skilled and professional migrants (expatriates), illegal migrants, refugees, asylum-seekers (Burmese asylum seekers with UNHCR card), forced migrants (human trafficking victims), students, and tourists.The influx of foreign nationals residing in Malaysia coincides with greater number of crime news featuring foreign nationals.This study explores the social construction of foreign nationals as the ‘other’ in the local crime news published by Malaysian newspapers.94 news headlines and lead sentences of local crime news involving foreign nationals were identified and analysed for this study.Findings suggest that Malaysian newspapers magnify foreign nationals’ migration status in each crime news.